2020
DOI: 10.1002/job.2470
|View full text |Cite
|
Sign up to set email alerts
|

The journey to leave: Understanding the roles of perceived ease of movement, proactive personality, and person–organization fit in overqualified employees' job searching process

Abstract: Summary Despite intensive research on perceived overqualification, empirical evidence on overqualified employees' job search behavior remains relatively insufficient. Notably, no studies have explored the possible link between perceived overqualification and internal job searching behaviors. In the present study, we consider whether—and more importantly when—employees with high perception of overqualification search for internal and external job opportunities. Applying the ability–motivation–opportunity (AMO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 70 publications
(225 reference statements)
0
30
0
Order By: Relevance
“…Although previous studies have not hypothesized and examined positive associations of proactive personality with P-J fit and P-O fit, Erdogan and Bauer's (2005) data showed positive correlations between proactive personality and both P-J fit and P-O fit. In addition, Wu and Chi's (2020) data also indicated that proactive personality is positively related to P-O fit. Based on this reasoning and the empirical evidence, the following hypotheses are presented.…”
Section: Theory and Hypothesesmentioning
confidence: 94%
“…Although previous studies have not hypothesized and examined positive associations of proactive personality with P-J fit and P-O fit, Erdogan and Bauer's (2005) data showed positive correlations between proactive personality and both P-J fit and P-O fit. In addition, Wu and Chi's (2020) data also indicated that proactive personality is positively related to P-O fit. Based on this reasoning and the empirical evidence, the following hypotheses are presented.…”
Section: Theory and Hypothesesmentioning
confidence: 94%
“…bring several adverse consequences to employees (Harari et al, 2017), such as more cyberloafing (Cheng et al, 2020), high turnover (Wu and Chi, 2020), and less proactive behavior (Luksyte et al, 2020).…”
Section: Hypothesis Development the Mediating Role Of Job Boredommentioning
confidence: 99%
“…We measured POQ with nine items using a scale adapted from Maynard et al (2006), which was commonly used in the POQ literature (Erdogan et al, 2020;Wu and Chi, 2020). A sample item was "I have job skills that are not required for this job" (α = 0.82).…”
Section: Perceived Overqualificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in personality traits affects the individual's cognition and perception of a social predicament, thus affecting the individual's choice of coping strategies. As a positive personality trait, a proactive personality – manifested as taking responsibility, caring for organizational interests, and optimism – may lead employees to exhibit variability in adopting knowledge-sharing behaviors in response to leader reward omissions (Wu and Chi, 2020). Therefore, we propose that a proactive personality weakens the negative relationship between leader reward omission and employee knowledge-sharing.…”
Section: Introductionmentioning
confidence: 99%